2021
DOI: 10.1111/dmcn.14842
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perspectives of pediatric powered wheelchair standing devices: a qualitative study

Abstract: AIM To explore and describe the experiences and perspectives of various stakeholders regarding the use of powered wheelchair standing devices (PWSDs).METHOD The purposive sample included: children aged 6 to 18 years who used a PWSD (n=8; diagnoses: cerebral palsy, spinal muscular atrophy, spina bifida, spinal cord injury), parents of children 18 years of age or younger who used a PWSD (n=12), rehabilitation professionals working with children who used a PWSD (n=12), and professionals working at companies manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
(121 reference statements)
1
7
0
Order By: Relevance
“…He was an appropriate candidate for the device, but was too small for it at the time. Our experiences were similar to those described by Kenyon et al 1 They explored stakeholder perspectives, which truly highlight both the benefits to participation and the realities of obtaining and owning this equipment.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…He was an appropriate candidate for the device, but was too small for it at the time. Our experiences were similar to those described by Kenyon et al 1 They explored stakeholder perspectives, which truly highlight both the benefits to participation and the realities of obtaining and owning this equipment.…”
supporting
confidence: 75%
“…My hope for my son with cerebral palsy (CP) is that he is included and can participate with his peers in the community, school, or home environment-and that he can have fun doing these things. When choosing equipment or devices to enhance participation, the factors we consider include: (1) Can it be used in multiple settings? (2) Can it operate with minimal assistance?…”
mentioning
confidence: 99%
“…70 A qualitative study exploring perceptions of standing power wheelchair use identified a similar theme. 115 'It is more than weight bearing' described perceived benefits for bowel, bladder, and respiratory function and BMD. In addition, psychological benefits were also seen as important with changes in how children were perceived when in their power standing devices.…”
Section: Supported Standing Can Help To Maintain or Improve Body Stru...mentioning
confidence: 99%
“…The ability to stand intermittently and frequently throughout the day may provide differing benefits from a separate stander. 115…”
Section: Supported Standing Provides An Important Position Change And...mentioning
confidence: 99%
“…For example, increas-ing autism spectrum disorder rates have been reported among individuals with SB utilizing a 31,220 subject population-based birth cohort [5,6]. Along with new clinical observations, telecommunication platforms such as Zoom ® have evolved as SB-related clinical and research tools [7]; from telemedicine to customized electronic medical records, technologies continue to be adapted for service in SB care [8,9]. To keep pace with the rapid transformations in our changing world, clinicians who serve the SB population must be able to turn to reliable sources of information and continuing medical education.…”
mentioning
confidence: 99%